THE INFLUENCE OF SERVICE QUALITY, RESTAURANT IMAGE, AND CUSTOMER PERCEIVED VALUE ONCUSTOMER SATISFACTION AND CUSTOMER LOYALTY IN RESTAURANT INDUSTRY (Study Case on Customer of Natural Strawberry Land and Resto, Lembang) - Chabsy Al Riezal Mutaqien; Sri Palupi Prabandari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This study aims to examine the effect of Service Quality, Restaurant Image, and Customer Perceived Value on Customer Satisfaction and Customer Loyalty in Natural Strawberry Land and Resto, Lembang. The path analysis, were conducted in order to acknowledge the direct and indirect relationships among the exogenous variables (service quality, restaurant image, and customer service value) on endogenous variables (customer satisfaction and customer loyalty).This study is explanatory research, in accordance with its purpose to describe the causal relationship among variables through hypothesis testing. The samples and populationof this study were the customers of Natural Strawberry Land and Resto, Lembang. In this study,the data collection method by distributing questitionaire. The sampling technique used is purposive sampling and the research instruments were tested using the validity test, reliability test, and classical assumption test and path analysis. The result of this study indicates that service quality, restaurant image, customer perceived value, and customer satisfaction significantly affect the customer loyalty. This study also shows that the customer considers getting the vacation that has high quality of service, a good value and a satisfactory experience. They also have quite a high intention to visit Natural Strawberry Land and Resto again in the future. Keywords: Service Quality, Restaurant Image, Customer Perceived Value, Customer Satisfaction, Customer Loyalty, Path analysis.